(De)Bonding with embryos: The emotional choreographies of Portuguese IVF patients - Delaunay, C.; Gouveia, L.; Santos, M.; Morais, R. (Social Science and Medicine, 2023)
In this article we develop the new concept of emotional choreography to describe how patients bond, debond and/or rebond with their embryos created in vitro using assisted reproductive technologies (ART). Using this concept, we explore how the patients' management of their own emotions intertwines with political, scientific, and religious factors. Our analysis relies on and further advances Thompson's concepts of ethical and ontological “choreography”. It is through these forms of choreography that complex contemporary biomedical issues with high political, ethical, and scientific stakes are negotiated, and through which different actors, entities, practices, roles, and norms undergo mutual constitution, reinforcement and (re)definition. Our article draws on the analysis of 69 in-depth interviews and the results of an online survey with 85 respondents.